A Mixed Methods Study of Graduate Students’ Achievement Motivation and Perceptions of Implementing Asynchronous Online Discussions - Dr. Rabab Mohammad Alareifi (Journal of Arts, Literature, Humanities and Social Sciences, 2023)
This study aims to examine the effect of asynchronous online discussions on female graduate students’ achievement motivation and to explore their perceptions toward it at a university in Saudi Arabia. A sequential explanatory mixed methods design was employed. Quantitative data were collected using a one-group pretest-posttest design, with an achievement motivation scale. The sample consisted of 10 purposefully selected students. Qualitative data were obtained through a focus group discussion with 8 students who completed the first phase and volunteered to participate in this phase. This study lasted for one semester and was grounded in Social Cognitive Theory. The results showed a positive effect of asynchronous discussions on achievement motivation, with a large effect size in perseverance, ambition, and perceived efficiency, but not in goal setting. Qualitative results revealed positive perceptions toward its usage. Benefits and strategies that instructors could implement to enhance the implementation of online discussions are discussed. Finally, implications and recommendations for future studies regarding the use of asynchronous online discussions are discussed.